(untitled) (African Journal of Law and Politics, 2025)
The importance of Transitional Justice in the context of Cameroon's ongoing socio-political crisis caused by the Boko Haram insurgence and the Anglophone crisis cannot be understated. Transitional Justice encompasses mechanisms that states, societies, and communities use to provide accountability and redress for gross human rights violations such as genocide, crimes against humanity, and war crimes. Despite adopting the statutory transitional justice measures to wits: justice, truth, reparation, and institutional reforms, Cameroon faces challenges in their effective implementation. This paper makes use of primary sources from laws and interviews and from secondary sources from books, articles and reports, to analyze the effectiveness of these mechanisms in Cameroon, particularly during the conflict period. The mechanisms lay the groundwork for peace and reconciliation and evaluates its coordination and effectiveness, analyzing reforms like the National Human Rights Commission, the Major National Dialogue, and the Disarmament, Demobilization, and Reintegration (DDR) Center. The effects of the current socio-political crisis reveal that there is lack of implementation of the transitional justice measures, which is fostered by ineffective coordination efforts. the paper highlights inter alia the urgent need for a robust legal framework to actualize transitional justice in Cameroon, drawing lessons from countries like South Africa and Rwanda, where context-specific approaches and inclusive processes for successful transitional justice.